Neonatal thyroid screening a tertiary care experience at VSS Medical College and Hospital, Burla - T. L., Vidhyadhara Naik; Panigrahi, Bineet; Panda, Sanjukta (International Journal of Contemporary Pediatrics, 2021)
Background: Congenital hypothyroidism is one of the most common preventable etiologies of mental retardation. The worldwide incidence of CH ranges from 1 in 3000 to 1 in 4000 live newborn. Objective of the study was to know the incidence of congenital hypothyroidism in this part of the country, which is necessary to understand the burden of congenital hypothyroidism to the society. Methods: Primary serum TSH measurement in screening neonates with backup thyroxine (T4) determination in infants with high TSH levels (>20 mIU/l). TSH and FT4 were estimated by chemi luminescence immunoassay (CLIA) method using reagent monobind, INC. Results: Serum TSH of screened neonates ranged between 0.16 mIU/l and 80.32 mIU/l, Mean±SD of sTSH being 5.80±3.96 mIU/l. Out of 2212 screened newborns, 9 newborns had sTSH value >20 mIU/l, who were recalled for confirmatory test, giving a recall rate of 0.4%. Out of 9 recalled newborns, 3 had persistently elevated sTSH >20 mIU/l making incidence of congenital hypothyroidism of 1:737 in our study. Conclusions: We found a higher incidence of 1:737 neonatal hypothyroidism in this region as compared to estimated national incidence. CH being preventable cause of mental retardation and other harmful effects on a growing newborn, neonatal screening programme for congenital hypothyroidism is highly recommended.